Mechanical injury accentuates lipid deposition in ApoE–/– mice and advance aortic valve stenosis: A novel modified aortic valve stenosis model - Wen, Dezhong; Hu, Li; Shan, Jianggui; Zhang, Hengyuan; Hu, Liuhua; Yuan, Ancai; Pu, Jun; Xue, Song (Frontiers in Cardiovascular Medicine, 2023)
Background Current mouse models still have limitations in studying aortic valve stenosis (AVS). A suitable animal model bearing a close resemblance to the pathophysiological processes of humans needs to be developed. Here, we combined two risk factors to create a mouse model that mimics the pathological features of human AVS. Methods and results We combined WI and hyperlipidemia in ApoE–/– mice to explore the synergistic effect on the stenosis of the aortic valve. Transthoracic echocardiography revealed progressively increased peak velocity with age in ApoE–/– mice to velocities above C57 mice when fed a high-fat diet after wire injury. Moreover, ApoE–/– mice demonstrated lower cusp separation and lower aortic valve area after 8 weeks vs. C57 mice. Gross morphology and MRI showed advanced thickening, sclerosis aortic valve, narrowing of the orifice area, and micro-CT showed obvious calcification in the aortic valves in the hyperlipidemia group after wire injury. Histopathology studies showed thickening and fibrosis of aortic valve leaflets in the hyperlipidemia group after wire injury. Notably, lipid deposition was observed in ApoE–/– mice 8 weeks after wire injury, accompanied by overexpressed apoB and apoA proteins. After wire injury, the hyperlipidemia group exhibited augmented inflammation, ROS production, and apoptosis in the leaflets. Moreover, the combination group exhibited advanced fibro-calcific aortic valves after wire injury. Conclusion Overall, we present the synergistic effect of wire injury and hyperlipidemia on lipoproteins deposition in the development of AVS in ApoE–/– mice, this model bear close resemblance to human AVS pathology.